Strong binding active constituents of phytochemical to BMPR1A promote bone regeneration: In vitro, in silico docking, and in vivo studies. Issue 8 (17th January 2019) - Rasoulian, Bita; Almasi, Amin; Hoveizi, Elham; Bagher, Zohre; Hayat, Parisa; Joghataei, Mohammad Taghi; Rezayat, Seyed Mahdi; Tavakol, Shima
Abstract: Two of the most problematic orthopedic and neurosurgeon visits are associated with spine and craniofacial fractures. Therefore, more attention needs to be paid to finding a medicine to repair these fractures. Amongst the most mysterious herbs, Aloe vera stands out. In the present study, the ameliorating function of A. vera on osteogenesis was studied in vitro and in vivo. Osteoblast‐like cells were exposed to A. vera, followed by analysis of cell viability, lactate dehydrogenase release, and intracellular reactive oxygen species (ROS) production. The results showed an enhanced cell biocompatibility in a dose‐dependent manner due to attenuated intracellular ROS production. Furthermore, a docking study indicated that the strong affinity of A. vera constituents to type I bone morphogenic protein receptor (BMPR1A) without the involvement of the BMPR1A chain B. The induction of osteogenesis prompts extracellular calcium deposition by osteoblasts, which affirms successful in vitro bone regeneration. However, injection of A. vera in rats with critical size calvarial defects induced Runx2, alkaline phosphatase (ALP), OCN, and BMP2 genes overexpression, which led to the formation of victorious bone with enhanced bone density and ALP activity. It is worthy to note that Aloin has the highest affinity to BMPR1A, whereas there are no reports regarding the impact of Aloenin, Aloesin, and γ‐sitosterol on osteogenesis. Furthermore, some of them have antitumor potency, and it might be proposed that they are considered as a bone substitute in the osteotomy site of osteosarcoma with the aim of bone recovery and suppression of osteosarcoma. The whole consequences of this investigation manifests the plausibility of using A. vera as an antioxidant and osteoconductive substitute. Abstract : Some Aloe vera constituents have antitumor potency, and it might be proposed that they are considered as a bone substitute in the osteotomy site of osteosarcoma with the aim of bone recovery and suppression of osteosarcoma. The whole consequences of this investigation manifest the plausibility of using A. vera as an antioxidant and osteoconductive substitute.